USIMPK. An Excel for Windows-based simulation program for instruction of basic pharmacokinetics principles to pharmacy students. Issue 3 (July 2015) - Brocks, Dion R.
Highlights A pharmacokinetics simulation teaching program is described. It is written in VBA in Excel for Windows. The program covers a wide variety of basic pharmacokinetic content. Students have responded favorably to its use.